Legal Certainty in the Exercise of Sanctioning Authority by the Notary Supervisory Council under the Indonesian Notary Office Act - Qolbi, M. Luthvi; Sakinah, Zurria (Al-Risalah, 2026)
This study examines legal certainty in the exercise of sanctioning authority by the Notary Supervisory Council under the Indonesian Notary Office Act (UUJN). The Council—comprising the Regional Supervisory Council (MPD), the Provincial Supervisory Council (MPW), and the Central Supervisory Council (MPP) is entrusted with preventive and repressive supervisory powers, including examining alleged violations and imposing administrative sanctions. However, ambiguities in the scope and coordination of sanctioning authority have led to inconsistent enforcement practices and raised concerns regarding legal certainty. Previous studies mainly examine supervisory structure, but rarely analyze sanction enforcement from a legal certainty perspective. Using a normative juridical method with statutory and conceptual approaches grounded in legal certainty theory, this research evaluates the coherence of the regulatory framework governing sanctions. This article argues that overlapping authority, procedural complexity, and interpretative inconsistencies weaken the principle of legal certainty and potentially affect both notarial protection and public trust. Strengthening regulatory clarity and institutional coordination is therefore essential to ensure consistent, proportional, and legally certain sanction enforcement.